O livro didático no contexto da formação do licenciado em Biologia: análise de projeto pedagógico de cursos - Pereira, Naomy Soares; Santos, Luís Henrique Oliveira; dos Santos, FrancisFrancisco de Assis Ribeiro (Educação, Escola & Sociedade, 2023)
Abstract: This research analyzed the pedagogical project of courses (PPC) of Licentiate in Biology at public institutions in the Northeast to raise the insertion of textbooks in the teacher training process. Thus, 36 courses from 29 institutions from all northeastern states have their PPC. The textbook (TB) has a greater presence in 27 courses, being indicated in disciplines and the competencies of the graduate. The TB was not identified in the design of the UFRN, URCA, and UEMA courses. The UEFS course is the only one to have a specific subject on TB, but in the IFPI the TB has a highlighted treatment. In the courses, the TB always appears with its role as a facilitator of learning with texts and activities in Science and Biology, without a social character in the formation of the citizen.